Data-Driven-Based Attribution of Runoff Changes in Tuwei River Basin in the Northern Windy-Sandy Region of Shaanxi - YU Huanghao; LI Binquan (Renmin Zhujiang)
The key point in analyzing the attribution of runoff changes is whether the natural runoff process of the basin can be accurately simulated.However,the application accuracy of hydrological models in arid and semi-arid regions of the Loess Plateau is generally not high.Taking the Tuwei River basin in the northern windy-sandy region of Shaanxi in the middle reach of the Yellow River as an example,this paper proposed an improved natural runoff simulation method based on the data-driven approach,so as to quantitatively analyze the effects of climate changes and human activities on runoff changes in the Tuwei River basin.The results show that the annual runoff series in the basin decreased significantly from 1961 to 2015,and there were two abrupt changes in 1979 and 1996,respectively.The annual runoff of the two periods (1980—1996 and 1997—2015) is 25.8% and 47.1% lower than that of the natural period (1961—1979),respectively.The runoff simulation accuracy of the three data-driven methods after improvement rises significantly.Specifically,the improved method proposed by Zhao Wenlin has the highest accuracy,and the Nash-Sutcliffe efficiency coefficient of annual runoff simulation in the natural period is 0.77.Climate change is the main reason for the significant decrease in the runoff between 1980 and 1996 (with a contribution of up to 80.9%).However,from 1997 to 2015,the contribution of climate change and human activities to the decrease in the runoff changed,with the influence of human activities increasing to a proportion of 58.8%.